Institutional Trap - Do, Quy-Toan (World Bank, Washington, D.C., 2013)
The author studies the persistence of inequality and inefficient governance in a physical capital accumulation model with perfect information, missing credit markets, and endogenous barriers to entry. When access to investment opportunities is regulated, rent-seeking entrepreneurs form coalitions of potentially varying size to bribe a regulator to restrict entry. Small coalitions run short of resources, while large coalitions suffer more severe free-rider problems. The distribution of wealth thus determines the equilibrium coalition structure of the economy and consequently the level of regulatory capture. A dynamic analysis supports the persistence of inefficiencies in the long run. Initial conditions determine whether the economy converges to a steady state characterized by efficient governance and low levels of inequality, or a path toward an institutional trap where regulatory capture and wealth inequality reinforce each other.